Resistance patterns of microbes isolated from gastrointestinal tract (Faculty of Medicine Universitas Indonesia, 2011)
Background: Digestive tract infection with clinical manifestation of diarrhea is an infectious disease that has the highest morbidity and mortality rate, especially in developing countries. Diarrhea causes mortality mostly in infants under one year old. Improvement in management is done continuously, but advances in diagnosis and therapy cannot be reached by developing countries. One of the etiological agents causing infection of digestive tract is bacteria. Therefore, knowledge of bacteria that cause gastrointestinal infection and their resistance patterns may support the management of this disease. The aim of this study was to examine microbes that were isolated from the digestive tract and their resistance patterns against antibiotics. Methods: Samples (stool, rectal/anal swab) were collected from the Clinical Microbiology Laboratory, FKUI during 2005-2008. Isolation, identifi cation and sensitivity test were conducted according to standard laboratory procedures. Interpretation of sensitivity test was done according to NCCLS/CLSI guidance. Data was analyzed using WHOnet version 5.3. Results: We found 28 isolates of pathogenic Escherichia coli, 1 isolate of S. paratyphi A and 4 isolates of yeasts. Pathogenic Escherichia coli were still sensitive against some antibiotics, but the sensitivity was reduced against amoxicillin, sulbenicillin, ticarcillin and trimethoprim/sulfamethoxazole. Conclusion: The most predominant gastrointestinal tract infection causing microbes was pathogenic Escherichia coli. These bacteria showed decrease sensitivity against some antibiotics commonly used to treat patients with gastrointestinal tract infection. (Med J Indones 2011; 20:105-8)